Maternagens na diáspora Amefricana: resistência e liminaridade em amada, compaixão e um defeito de cor - Silva, Danielle de Luna e (2017)
This research aims at analyzing, from a transnational and historical perspective, mothering practices in Beloved, A Mercy and Um defeito de cor as acts of resistance against the objectification and appropriation of the black female body by the institution of slavery in the United States and in Brazil. These novels written by Toni Morrison (Beloved and A Mercy) and Ana Maria Gonçalves (Um defeito de cor) can be considered as part of the genre known as neo-slave narratives or contemporary narratives of slavery, fictional texts that revisit and recreate the first slave narratives. Widely popular in the 18th century, these texts written by formerly enslaved men and women, sometimes with the help of an amanuensis, presented their stories about the experience of life under slavery. Less concerned with the accurate reproduction of historical facts, Gonçalves and Morrison give voice to the “interior life” of their characters, enslaved women who resort to different strategies in order to resist a system which aimed at their commodification. Thus, these texts present new paradigms of black mothering in the Amefrican Diaspora, depicting mothering as means of bonding with the community and of female empowerment. These narratives emphasize the struggle mothers experience to preserve and protect their children, in line with what is proposed by Patricia Hill Collins and Andrea O’Reilly regarding the specificities of black motherhood/mothering. Moreover, a strong presence of African religious and cultural practices can be observed in these novels, which permeate and have an impact on the relationship between mothers and their children, justifying the use of the term Amefrican, which connects America and Africa in a transnational context. Abikus and Ogbanjes, children with strong connections with the world of spirits, and Ibejis, twins, are interpreted here as liminal beings which enact not only potential ruptures, but also (re)connections between mothers and their children, and between Africans and their descendants in the Black Diaspora and the African continent. Therefore, the association between mothering and resistance, as well as the discussion about the fluid borders between the world of the living and of spirits, between Africa and America, guided our analysis of the three novels, which indicate alternative paths, fictionally construed, in which empowering is seen as a result of blood, cultural and religious connections.